Physicians' Perspectives on Palliative Care for Patients With End‐Stage Liver Disease: A National Survey Study. Issue 6 (3rd May 2019) - Ufere, Nneka N.; Donlan, John; Waldman, Lauren; Patel, Arpan; Dienstag, Jules L.; Friedman, Lawrence S.; Corey, Kathleen E.; Hashemi, Nikroo; Carolan, Peter; Mullen, Alan C.; Thiim, Michael; Bhan, Irun; et al.
Abstract : Specialty palliative care (PC) is underused for patients with end‐stage liver disease (ESLD). We sought to examine attitudes of hepatologists and gastroenterologists about PC for patients with ESLD. We conducted a cross‐sectional survey of these specialists who provide care to patients with ESLD. Participants were recruited from the American Association for the Study of Liver Diseases membership directory. Using a questionnaire adapted from prior studies, we examined physicians' attitudes about PC and whether these attitudes varied based on patients' candidacy for liver transplantation. We identified predictors of physicians' attitudes about PC using linear regression. Approximately one‐third of eligible physicians (396/1236, 32%) completed the survey. Most (95%) believed that centers providing care to patients with ESLD should have PC services, and 86% trusted PC clinicians to care for their patients. Only a minority reported collaborating frequently with inpatient (32%) or outpatient (11%) PC services. Most believed that when patients hear the term PC, they feel scared (94%) and anxious (87%). Most (83%) believed that patients would think nothing more could be done for their underlying disease if a PC referral was suggested. Physicians who believed that ESLD is a terminal condition (B = 1.09; P  = 0.006) reported more positive attitudes about PC. Conversely, physicians with negative perceptions of PC for transplant candidates (B = –0.22; standard error = 0.05; P  < 0.001) reported more negative attitudes toward PC. In conclusion, although most hepatologists and gastroenterologists believe that patients with ESLD should have access to PC, they reported rarely collaborating with PC teams and had substantial concerns about patients' perceptions of PC. Interventions are needed to overcome misperceptions of PC and to promote collaboration with PC clinicians for patients with ESLD.